3
$\begingroup$

So the equation is $3\cos ^2t + 5\sin t = 1$

Now I have simplified this to $$3(1-\sin ^2t) + 5\sin t -1 = 0$$ which leads to $$-3\sin ^2t + 5\sin t + 2 = 0$$ Then I get $$-3t^2 + 5 t +2 = 0$$

Is this the correct way to go with this equation then use $t = t/2 \pm \sqrt {(t/2)^ 2 + y}$ where $y$ in this case will be $2/3$ ?

$\endgroup$
  • $\begingroup$ Please clarigy your question. Why you used $t$ in both cases? $\endgroup$ – Michael Galuza Jul 26 '15 at 5:33
  • $\begingroup$ your third and four steps are not good $\endgroup$ – Chiranjeev_Kumar Jul 26 '15 at 5:35
  • $\begingroup$ I use t because it says so in my textbook. The question is solve the equation $3*\cos ^2t + 5*\sin t = 1$ and if the third and fourth step are bad then there should be another identity to use i guess.^ Thanks for your fast replies. $\endgroup$ – addde Jul 26 '15 at 5:36
  • 1
    $\begingroup$ The original equation is expressed in terms of $t$, so if you are to make a substitution, it is a good idea to use a different variable, i.e. let $x=\sin(t)$, so you have got $-3x^2+5x+2=0$ $\endgroup$ – user265675 Jul 26 '15 at 5:40
7
$\begingroup$

$$3\cos ^2t + 5\sin t = 1$$

$$3(1-\sin ^2t) + 5\sin t -1 = 0$$

$$-3\sin ^2t + 5\sin t + 2 = 0$$

$$3\sin ^2t - 5\sin t - 2 = 0$$

Now , Let $\sin t =x$, then equation reduces to,

$$3x^2-5x-2=0$$

$$(3x+1)(x-2)=0$$, Now can you finish from here?

$\endgroup$
  • $\begingroup$ Yes i can thanks for your help $\endgroup$ – addde Jul 26 '15 at 5:51
  • $\begingroup$ @addde: you are welcome :) $\endgroup$ – Chiranjeev_Kumar Jul 26 '15 at 5:53
2
$\begingroup$

you have $$-3\sin(t)^2+5\sin(t)+2=0$$ let $$\sin(t)=u$$ then we have $$-3u^2+5u+2=0$$ divided by $-3$ gives $$u^2-\frac{5}{3}u-\frac{2}{3}=0$$ solving this equation we obtain $$u_{1,2}=\frac{5}{6}\pm\sqrt{\frac{25}{36}+\frac{24}{36}}$$ from here you will come to the result.

$\endgroup$
2
$\begingroup$

We have, $$3\cos ^2t + 5\sin t = 1$$ $$\implies 3(1-\sin ^2t) + 5\sin t = 1$$ $$\implies 3\sin ^2t+ 5\sin t-2=0$$ Factorizing the expression, we get $$ (3\sin t-1)(\sin t+2)=0$$ $$\text{if}\ 3\sin t-1=0 \implies \sin t=\frac{1}{3}$$$$\implies \color{blue}{t=2n\pi+\sin^{-1}\left(\frac{1}{3}\right)}$$ $$\text{Or} \ \color{blue}{t=(2n+1)\pi-\sin^{-1}\left(\frac{1}{3}\right)}$$ $$\text{if}\ \sin t+2=0 \implies \sin t\neq -2$$ Hence, the general solution is $t=2n\pi+\sin^{-1}\left(\frac{1}{3}\right)$ or $t=(2n+1)\pi-\sin^{-1}\left(\frac{1}{3}\right)$

Where, n is any natural number

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.